2016
DOI: 10.21839/jaar.2016.v1i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NaCl salinity on plant growth and nutrient assimilation of Zea mays L.

Abstract: Maize (Zea mays L.) is the world's leading edible oil and third largest important cereal. In addition to it is used as food for human consumption as well as food grain for livestock. High concentrations of NaCl in soils account for large decrease in the yield of a large variety of crops all over the globe. The objective of the present study was conducted to evaluate NaCl stress on growth and mineral nutrient composition of maize plants. Maize seeds were grown in plastic pots having fine sand. After 20 days of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Treatment W2 recorded an average of (6.67) and it differed significantly from treatment W4 with an increase of (103.3)% respectively. These results are consistent with what was found (Sozharajan and Natarajan, 2016). As for the bilateral interaction, where treatment W1S1 recorded the highest average of (14.60) and the lowest average of treatment W4S0 reached (2.09).…”
Section: K: Na Ratiosupporting
confidence: 92%
See 1 more Smart Citation
“…Treatment W2 recorded an average of (6.67) and it differed significantly from treatment W4 with an increase of (103.3)% respectively. These results are consistent with what was found (Sozharajan and Natarajan, 2016). As for the bilateral interaction, where treatment W1S1 recorded the highest average of (14.60) and the lowest average of treatment W4S0 reached (2.09).…”
Section: K: Na Ratiosupporting
confidence: 92%
“…The results of the statistical analysis in table (1) showed that there were significant differences when adding different levels of silicon, where treatment S1 recorded the lowest average sodium concentration and amounted to (0.50)%, respectively, with a decrease of (46%) compared with the comparison treatment S0, which recorded an average of (0.73)%, and the reason was attributed That silicon reduces sodium absorption, these results are consistent with (Farooq et al, 2019). As for the levels of irrigation water, where the highest average concentration of sodium in treatment W4 was (0.96%) than the rest of the treatments W1, W2 and W3, an increase of (231.0, 92 and 37.1)%, respectively, as well as the W3 treatment, which recorded an average of (0.70)% compared to treatments W1 and W2 with an increase of (141.1 and 40%) that the increase of sodium with the increase in the salinity of the irrigation water because of the increase in the concentration of sodium and this was confirmed by (Sozharajan andNatarajan, 2016 andAl-Shammari, 2021). As for the interaction between silicon and irrigation water, where treatment W4S0 recorded the highest average sodium concentration amounted to (1.36%) and treatment W1S1 recorded the lowest average sodium concentration amounted to (0.24)%.…”
Section: The Concentration Of Sodium In the Plantmentioning
confidence: 52%
“…When toxic ions are continually sequestered into vacuoles, organic solutes that are compatible with the cells metabolic activities must be accumulated within the cytosol and organelles to balance osmotic pressure (Munns et al, 2016;Yang & Guo, 2018). Compatible solutes or osmo-protectants are of low molecular mass and well soluble compounds that are typically non-toxic at high cellular concentrations (Sozharajan & Natarajan, 2016). Compatible osmolytes may also reduce water loss and enhance cell turgor and cell expansion.…”
Section: Tissue Tolerancementioning
confidence: 99%
“…Compatible osmolytes may also reduce water loss and enhance cell turgor and cell expansion. Common osmolytes include proline, sucrose, polyols, mannitol, glucose, fructose and sucrose (Yang & Guo, 2018) (Sozharajan and Natarajan, 2016). Proline accumulation induced by NaCl has been shown to correlate with salinity induced growth inhibition.…”
Section: Tissue Tolerancementioning
confidence: 99%
See 1 more Smart Citation